Functional Connectivity of the Human Paraventricular Thalamic Nucleus: Insights From High Field Functional MRI - Kark, Sarah M.; Birnie, Matthew T.; Baram, Tallie Z.; Yassa, Michael A. (Frontiers in Integrative Neuroscience, 2021)
The paraventricular thalamic nucleus (Pvt) is a small but highly connected nucleus of the dorsal midline thalamus. The Pvt has garnered recent attention as a context-sensitive node within the thalamocortical arousal system that modulates state-dependent motivated behaviors. Once considered related to generalized arousal responses with non-specific impacts on behavior, accumulating evidence bolsters the contemporary view that discrete midline thalamic subnuclei belong to specialized corticolimbic and corticostriatal circuits related to attention, emotions, and cognition. However, the functional connectivity patterns of the human Pvt have yet to be mapped. Here we combined high-quality, high-resolution 7T and 3T resting state MRI data from 121 young adult participants from the Human Connectome Project and thalamic subnuclei atlas masks to investigate resting state functional connectivity of the human Pvt. The 7T Results demonstrated extensive positive functional connectivity with the brainstem, midbrain, ventral and dorsal medial prefrontal cortex (mPFC), anterior and posterior cingulate, ventral striatum, hippocampus, and amygdala. These connections persist upon controlling for functional connectivity of the rest of the thalamus. Whole-brain contrasts provided further evidence that, compared to the rest of the thalamus or three nearby midline thalamic subnuclei, functional connectivity of the Pvt is strong with the hippocampus, amygdala, ventral and dorsal mPFC, and middle temporal gyrus. These findings suggest that, even during rest, the human Pvt is functionally coupled with many regions known to be structurally connected to rodent and non-human primate Pvt. Further, cosine similarity analysis results suggested the Pvt is integrated into the default mode network (DMN), an intrinsic connectivity network associated with episodic memory and self-referential thought. The current work provides a much-needed foundation for ongoing and future work examining the functional roles of the Pvt in humans.